Two new species of Stylopoma (Bryozoa, Cheilostomatida) from the Southwestern Atlantic - Rodrigues, Maria J.s.; Larré, Igor R.n.m.; Vieira, Leandro M. (Zootaxa, 2024)
Two new species of the cheilostomate bryozoan genus Stylopoma are described from Brazil—Stylopoma anacarolinae sp. nov. and Stylopoma priscilae sp. nov. Stylopoma anacarolinae sp. nov. exhibits zooids with single or paired small avicularia and an orifice with a U-shaped sinus, in contrast to the long avicularia and orifice with a teardrop-shaped sinus of Stylopoma priscilae sp. nov. In addition to taxonomic description, a revised comparative table of living species worldwide is provided.